Detecting low concentration of H2S gas by BaTiO3 nanoparticle-based sensors - Huang, He-Ming; Li, Hua-Yao; Wang, Xiao-Xue; Guo, Xin (Sensors and actuators. B, Chemical, 2017)
Ce-doped BaTiO3 (Ba0.99Ce0.01TiO3) nanoparticles with the sizes of 30–60nm were prepared by the co-precipitation method, and sensors were fabricated by spin coating the nanoparticles on FTO substrates. To further enhance the sensing properties, α-Fe2O3 was decorated to the Ba0.99Ce0.01TiO3 sensor. The Fe2O3-Ba0.99Ce0.01TiO3 sensor showed fascinating gas sensing performances towards H2S, including the ability to detect low concentrations of H2S (400ppb or lower), fast response and recovery speed (tres=45s and trec=124s) and low working temperatures (150°C). When exposed to H2S, the sensor resistance increased, due to the reduction of Ce4+ to Ce3+ and the chemical reactions of oxygen species.